Using Dynamic Contextual Factors to Better Understand the Etiology and Escalation of Stalking Violence - Thompson, Carleen M. (Criminal justice and behavior, 2020)
Stalking is dynamic, influenced by targets’ reactions and stalkers’ circumstances. Consequently, the risk of violence in stalking cases is likely dynamic. Despite this, dynamic contextual factors have been neglected in stalking violence research. Guided by Thompson’s integrated theoretical model, we investigated key established stalking violence risk factors alongside new dynamic contextual factors in a content analysis of 43 stalking court transcripts from Queensland, Australia. Findings suggest that relying on individual factors in isolation leads to moderate rates of error. Combining risk factors provides a more sophisticated understanding of stalking violence, with dynamic contextual factors playing a pivotal role in understanding changes in risk, including when stalkers with historical and/or static contextual factors pose a higher risk of violence. Findings emphasize the need to look beyond traditional dispositional, historical, and static factors toward new dynamic contextual factors and highlight the importance of contextual factors for violence assessment and prevention strategies.